Legal Effectiveness In Providing Consumer Protection For Online Sales And Purchase At Ecommerce - Ferroka Putra Wathan (Publikasi Indonesia, 2023)
The rise of cases of goods that do not match the image that consumers see in the marketplace shows how weak consumers are in terms of buying and selling online. However, that does not mean that sellers may sell products without following the applicable regulations. Consumers have the right to get clear information about the product they buy. So, the form of responsibility that they should give to consumers is the return of goods or a refund. It means that they will still be responsible for losses that have been received by consumers with the return procedure, but what is done by online buying and selling business actors. In this study is not in accordance with Article 19 of Law No. 8 of 1999 concerning Consumer Protection: a) Business actors in charge of compensating consumers for losses, pollution, or losses incurred as a result of consuming produced or traded goods or services; b) Pay as alluded to in section (1) might be as a discount or substitution of labor and products of the equivalent or identical worth, or clinical treatment or pay as per the arrangements of the relevant regulations; c) The payment is made within seven days of the transaction's date; d) Despite the mentions in paragraphs (1) and (2), the possibility of a criminal charge based on additional evidence indicating the existence of an element of guilt remains;